Ambulatory and silent myocardial ischemia in women with coronary microvascular dysfunction: Results from the Cardiac Autonomic Nervous System study (CANS). (1st October 2020) - Roy, Rajasree; Aldiwani, Haider; Darouian, Navid; Sharma, Shilpa; Torbati, Tina; Wei, Janet; Nelson, Michael D.; Shufelt, Chrisandra; Minissian, Margo B.; Li, Lian; Merz, C. Noel Bairey; Mehta, Puja K.
Abstract: Background: Up to two-thirds of patients with obstructive coronary artery disease (CAD) have silent ischemia (SI), which predicts an adverse prognosis and can be a treatment target in obstructive CAD. Over 50% of women with ischemia and no obstructive CAD have coronary microvascular dysfunction (CMD), which is associated with adverse cardiovascular outcomes. We aimed to investigate the prevalence of SI in CMD in order to consider it as a potential treatment target. Methods: 36 women with CMD by coronary reactivity testing and 16 age matched reference subjects underwent 24-h 12-lead ambulatory ECG monitoring (Mortara Instruments) after anti-ischemia medication withdrawal. Ambulatory ECG recordings were reviewed by two-physician consensus masked to subject status for SI measured by evidence of ≥1 minute horizontal or downsloping ST segment depression ≥1.0 mm, measured 80 ms from the J point. Results: Demographics, resting heart rate, and systolic blood pressure were similar between CMD and reference subjects. Thirty-nine percent of CMD women had a total of 26 SI episodes vs. 0 episodes in the reference group (p = 0.002). Among these women 13/14 (93%) had SI, and few episodes (3/26, 12%) were symptomatic. Mean HR at the onset of SI was 96 ± 13 bpm and increased to 117 ± 16 bpm during the ischemic episodes. 87% reported symptoms that were not associated with ST depressions. Conclusions: Ambulatory ischemia is prevalent in women with CMD, with a majority being SI, while most reported symptoms were not accompanied by ambulatory ischemia. Clinical trials evaluating anti-ischemic medications should be considered in the CMD population. Highlights: Silent ischemia (SI) is prevalent in women with coronary microvascular dysfunction (CMD) compared to reference controls. SI occurs in CMD at heart rates similar to obstructive CAD population. Symptoms of CMD were not accompanied by ambulatory ischemia. Treatment of SI with anti-ischemic therapy could be a potential treatment for CMD.